(untitled) (Journal of Engineering, 2025)
The qualities of both fresh and hardened perlite self-compacting concrete are assessed in this study. The self-compacting concrete mix utilized in this investigation included 594 kg/m3 of binder. Four concrete mixes were tested with perlite used in place of some of the coarse aggregate at volumetric ratios of (0, 20, 40, and 50) %. Slump flow, V-funnel, L-Box, and segregation index tests were used to evaluate the properties of fresh concrete. At 56 days after burning, hardened concrete is tested. These tests gauge a material’s flexural, splitting, and compressive strengths. According to the data perlite content reduces workability. The percentage of perlite increases causes a considerable decrease in the compressive, flexural, and splitting tensile strengths when compared to the reference mixture. Following their burning at (300, 500, and 700 °C), half of the specimens cooled gradually before being tested, while the other half cooled rapidly. The residual percentages of Compressive strength at 56 days after burning were the most at 50% perlite, with (89.75,65.21, and 42.86) % at 300, 500, and 700 Co, respectively for gradual cooling. The residual percentages of Splitting tensile strength at 56 days after burning for PG50% were (98.85,85.22and 51.31) % at 300, 500, and 700 Co, respectively for gradual cooling.